Learning correspondences between magnitudes, symbols and words: evidence for a triple code model of arithmetic development - Malone, SA; Heron-Delaney, M; Burgoyne, K; Hulme, C (Elsevier, 2019)
According to the Triple Code Model, early arithmetic development depends on learning the mappings between non-verbal representations of magnitude (quantity) and symbolic verbal (number words) and visual (Arabic numerals) representations of number. We examined this hypothesis in a sample of 166 4- to 7-year old children. Children completed 4 paired-associate learning tasks and a broad range of measures assessing early numerical (symbolic and non-symbolic magnitude comparison, digit writing, arithmetic) and reading skills (letter-sound knowledge, phoneme awareness, rapid automatized naming, word reading). A path model showed that paired-associate learning tasks involving mapping magnitudes onto verbal or visual stimuli predicted arithmetic performance over and above other well-established predictors. This relationship was specific to arithmetic and, consistent with the Triple Code Model, highlights that mapping between non-symbolic magnitude representations and the corresponding symbolic forms (verbal and visual) is important to the development of arithmetic skills.